The combined administration of systemic and topical tranexamic acid for total hip arthroplasty: Is it better than systemic? - Deniz Gulabi; Yucel Yuce; Kutlu Hakan Erkal; Necdet Saglam; Savas Camur (Acta Orthopaedica et Traumatologica Turcica, 2019)
Obective: The aim of this study was to evaluate the effect of combined intravenous and topical use of tranexamic acid (TXA) on total blood loss and transfusion rate in total hip arthroplasty. Methods: This prospective randomized study included 57 patients who had undergone total hip arthroplasty between September 2016 and September 2017. The IV administration group (Group 1) consisted of 26 patients (mean age: 63.73 ± 10.29 years), while the IV and topical administiration group (Group 2) consisted of 22 patients (62.82 ± 8.31 years). Demographic data and outcomes were obtained through a review of individual medical records. Medical comorbidities, body mass index (BMI), ASA and CCI, preoperative and postoperative hemoglobin levels, postoperative transfusion records and 90-day joint-related (implant subsidence, dislocation, postoperative anemia, deep infection, hematoma and/or wound problem, postoperative periprosthetic fracture) readmission rate and complication rate were compared between the groups. Results: No significant differences were observed between the 2 groups in terms of age, gender, height, weight, body mass index (BMI), the level of preoperative Hb values, and the American Society of Anesthesiologists (ASA) and Charleson Comorbidty Index (CCI) rating (p > 0.05). The mean postoperative Hgb in the group 2 was higher by a small amount compared to the group 1. No statistically significant difference was determined between the groups in respect of the Hgb values (p = 0.562). Hgb Delta in the group 2 was lower than that of the group 1. The difference between the groups in the Hgb Delta values was not statistically significant (p = 0.268). The mean total blood loss was lower in the group 2 than in the group 1 but the difference was not statistically significant (p = 0.788). There was no significant difference observed in terms of any adverse complications among the 2 groups (p > 0.05). Conclusion: The combined administration of IV and topical TXA compared with IV alone can decrease total blood loss and the number of blood transfusions required without increasing the risk of DVT or/and PE in total hip arthroplasty. But the statistical analysis and clinical relevance is not significant. Level of Evidence: Level I Therapeutic Study. Keywords: Hip arthroplasty, Blood loss, Hgb, TXA, DVT